2007
DOI: 10.2307/25549736
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Social Connectedness, Communication and Monitoring on Adolescent Sexual Activity in Ghana

Abstract: This paper examines connectedness to, communication with and monitoring of unmarried adolescents in Ghana by parents, other adults, friends and key social institutions and the roles these groups play with respect to adolescent sexual activity. The paper draws on 2004 nationallyrepresentative survey data and qualitative evidence from focus group discussions and in-depth interviews with adolescents in 2003. Adolescents show high levels of connectedness to family, adults, friends, school and religious groups. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
97
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 11 publications
14
97
1
1
Order By: Relevance
“…Parental control is associated with later first sex, with having fewer than two sex partners in the past 12 months for boys and girls, and with condom use at first sex for girls. These findings are in line with the results of other studies which have shown that parental control is less likely to be associated with sexual relations in the past months [13] [15] and more likely to be associated with using a condom at most recent sexual relation [50]. However, our study demonstrates that parental control is less likely to be associated with systematic condom use in the past 12 months.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Parental control is associated with later first sex, with having fewer than two sex partners in the past 12 months for boys and girls, and with condom use at first sex for girls. These findings are in line with the results of other studies which have shown that parental control is less likely to be associated with sexual relations in the past months [13] [15] and more likely to be associated with using a condom at most recent sexual relation [50]. However, our study demonstrates that parental control is less likely to be associated with systematic condom use in the past 12 months.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, boys who initiated sex at an early age where more likely to report having talked about sexuality with family members. Babalola et al [12], Kumi-Kyereme et al [13] and Biddlecom et al [15] obtained similar results.…”
Section: Discussionmentioning
confidence: 61%
“…A third possibility is they may not experience parental monitoring to the same extent as non-orphaned adolescents. 55 The qualitative data provide insight into how unwanted sex takes place: through force, the giving of money or gifts, flattery, wearing the female down or threatening have sex with other girls, and passive acceptance. Transactional sex was more prevalent in the interviews from Uganda than in Malawi.…”
Section: Discussionmentioning
confidence: 99%
“…In designing the questions, a literature search was conducted on the topic to identify relevant questions and concepts on sexual and reproductive health among adolescents. Questions from different studies [30][31] conducted on reproductive health in general and adolescent reproductive health informed the current study. The rationale for adopting and adapting aspects of questionnaires used in previous studies was to ensure that the variables used conformed to standardised meaning and measurements.…”
Section: Methodsmentioning
confidence: 99%